Pengaruh Popularitas Media Sosial Perusahaan Terhadap Asimetri Informasi pada Perusahaan LQ45 - Liyanto, Liyanto; Ainun, Moh. Baqir (Politeknik Ganesha Medan, 2024)
Information asymmetry can have many negative impacts in the business world, such as moral hazard, monitoring costs, financial ineffectiveness, financial crises, company bankruptcy, and investment decision making errors by investors. Information asymmetry can be reduced by information transfer and communication. In the technological era, this information can be conveyed via digital platforms such as social media. Social media has recently become a company's main concern to support business performance. The important role of social media is not only felt in increasing market share but has been proven to help companies increase company value. The aim of this research is to prove the impact of social media popularity on information asymmetry in LQ45 companies in Indonesia. This research is important to conduct to obtain empirical evidence of the impact of social media popularity on company information asymmetry in Indonesia. So far, studies on the popularity of social media still occur in many developed countries and have not been carried out much in developing countries, including Indonesia. Using a sample of 99 company-years, the data was analyzed using multiple regression analysis. The research results show that company social media (Facebook, Instagram and Twitter) have an effect on information asymmetry, while YouTube has not been proven to have an effect on information asymmetry. This research contributes in several ways. First, this research adds scientific insight into the impact of social media on the business sector. Second, this research can be a reference for stakeholders, especially company managers, to consider managing social media optimally, especially to reduce information asymmetry